Nepal's cash allowances for children with disabilities - Rebecca Holmes; Fiona Samuels; Anita Ghimire; Stefan Thewissen (Overseas Development Institute (ODI), 2018)
Nepal's disability allowance is one of five government-run social security allowance schemes. It is part of the government's approach to promote the inclusion and welfare of people with disabilities, providing regular cash transfers to people who hold the national disability card. This report describes the experiences of children with disabilities and their caregivers in Nepal, including their experience of the 2015 earthquakes, and examines the barriers faced in accessing the disability allowance. Based on this analysis, we provide specific policy recommendations to overcome the high exclusion rates from the scheme, and how the scheme can be used in the future to support emergency relief efforts.
Keywords: 330